2015
DOI: 10.1159/000381204
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Interprofessional Collaboration

Abstract: This chapter underscores the importance of interprofessional collaboration in the care of frail older patients. Hospital-based care is emphasized because interprofessionalism is difficult in that setting since the setting is constantly changing and since multiple healthcare professionals care for many complex, very ill patients, only some of whom are frail older people. Interprofessionalism is particularly important and challenging in teaching units in the acute care setting, where many health professionals pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…From a macroscopic perspective, policymakers should be able to foresee the upcoming changes in demographic structure and allocate resources to facilitate the prevention and care of chronic diseases. Furthermore, interprofessional collaboration is not only limited to disease management, but is an inevitable element in solving everyday problems, such as poverty, climatic change, pollution, and discrimination (Sutton and Kemp, 2006;Briggs and McElhaney, 2015;Kostoff et al, 2016;Bryant et al, 2017). As the pillars of society, university graduates should demonstrate the competency of sharing their expertise and making a contribution to the team.…”
Section: Discussionmentioning
confidence: 99%
“…From a macroscopic perspective, policymakers should be able to foresee the upcoming changes in demographic structure and allocate resources to facilitate the prevention and care of chronic diseases. Furthermore, interprofessional collaboration is not only limited to disease management, but is an inevitable element in solving everyday problems, such as poverty, climatic change, pollution, and discrimination (Sutton and Kemp, 2006;Briggs and McElhaney, 2015;Kostoff et al, 2016;Bryant et al, 2017). As the pillars of society, university graduates should demonstrate the competency of sharing their expertise and making a contribution to the team.…”
Section: Discussionmentioning
confidence: 99%
“…3,[9][10][11][12][13][14] These approaches build on growing evidence that highlights the importance of team-based care delivery in ensuring that care practices are patient-centred, safer, timelier and more effective. [15][16][17][18][19] Despite the emergence of interprofessional teams as an effective approach to caring for older people, [20][21][22][23] little is known about how HCPs, including those outside the traditional roles of prescribing, distribution and administration of medication, individually recognize and respond to polypharmacy within their clinical practice. Central to the success of a collaborative interprofessional polypharmacy mandate is an understanding of how each HCP understands their individual and collective roles and responsibilities in managing polypharmacy.…”
Section: B Farrellmentioning
confidence: 99%
“…The rise of chronic and complex conditions is a matter of global activity, yet this area of practice is often overlooked in the literature (Briggs & McElhaney, 2015). This study found the 'essence' of complex care nursing to be an emergent, interwoven, relational and dynamic form of nursing practice, that continuously shaped the lifeworld of each participant.…”
Section: Discussionmentioning
confidence: 89%
“…Her response to a pressured environment was that of ‘time management…prioritization’, and ‘organizing’. However, this perspective leaves open the question of what warrants de‐prioritization in a time‐constrained context, and the effects of truncating nursing time with patients (Berg & Danielson, 2007; Briggs & McElhaney, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation